Exploring the experiences of healthcare workers in delivering spiritual care to patients in shari’ah compliance hospital - Wan Mamat, Wan Hasliza; Hairulisa @ Mohd Hairi, Nur Alia; Mohamad Shariff, Nurasikin; Che Ahmad, Aminudin; Jaafar, Siti Nur Illiani; Salah, Machouche (Panyapiwat Institute of Management (PIM), 2024)
Spiritual care is an integral component of healthcare workers’ roles, encompassing the recognition and addressing of patients’ spiritual needs, as well as providing support for their emotional and psychological well-being. Moreover, facilitating connections to resources or support systems that align with patients’ beliefs and values is paramount. Despite its importance, there is currently a scarcity of literature on healthcare workers’ experiences in delivering spiritual care. This study aimed to explore the experiences of healthcare workers in delivering spiritual care to patients in a hospital. A qualitative study was conducted among healthcare workers at a Shari’ah Compliance Hospital in Malaysia. A semi-structured interview was used to collect data from May 2023 until November 2023. All interviews were recorded, transcribed, and analysed using thematic analysis. Ten participants with diverse backgrounds agreed to take part in the study. Two main themes emerged from the analysis: 1) patient's response, and 2) spiritual concerns. The findings shed light on the varied experiences of healthcare workers when delivering spiritual care to patients within a hospital setting. This study revealed that healthcare workers were going through different experiences in delivering spiritual care. These findings have important implications for healthcare practice, highlighting the need for ongoing education and training in spiritual care competencies for healthcare workers. Addressing the spiritual needs of patients is crucial for providing holistic and patient-centered care.